THEORETICAL AND CONCEPTUAL ESSENCE OF STRATEGY AND STRATEGIC BUSINESS MANAGEMENT IN THE MODERN ECONOMY (International Journal of Innovative Technologies in Economy, 2020)
The purpose of the scientific research is to study the theoretical and conceptual aspect of strategy and strategic management in the operation of private business, and develop recommendations on their actual interpretation in the modern economy. The methodological aspect of the work is formed by theoretical conclusions and generalizations of the economic science and scientific works on the basis of strategy and strategic management in the operation of private business. The work applies logical, comparative and complex approaches as well as empirical research, comparison and complex analysis methods.During the research, significant scientific developments regarding the core of strategy and strategic management were analyzed and structured. The aspects of the main structural elements of the strategy were described: policy, tactics, management procedures, planning and budgeting. The essence of the subject (solutions), which are recommended for creating effective business management strategies, is proposed. Scientific approaches to understanding the core of strategic management are studied.On the basis of the conducted research, scientific approaches to strategy and strategic management are offered to group on the basis of complexity and the consideration of aspects of enterprise activity on: point approaches, approaches of relativity, panoramic approaches. The author's definition of the concept of "strategy" and "strategic management" is presented and the attention is focused on their short-, medium- and long-term perspective.The scientific value of the research results lies on their focus on solving the problem of searching for the concepts of an effective strategy and strategic business management, which can ensure the competitiveness and improvement of the financial results of the private sector, as well as the growth of the national economy.